Head shaking does not alter vestibulo ocular reflex gain in vestibular migraine - Patel, Priyani; Castro, Patricia; Koohi, Nehzat; Arshad, Qadeer; Gargallo, Lucia; Carmona, Sergio; Kaski, Diego (Frontiers in Neurology, 2022)
Vestibular Migraine (VM) is the most common cause of non-positional episodic vestibular symptoms. Patients with VM commonly report increased motion sensitivity, suggesting that vestibular responses to head movement may identify changes specific to VM patients. Here we explore whether the vestibulo-ocular reflex (VOR) gain alters in response to a clinical ‘headshake’ manoeuvre in patients with VM. Thirty patients with VM in the inter-ictal phase, sixteen patients with Benign Positional Paroxysmal Vertigo (BPPV) and fifteen healthy controls were recruited. Patients responded to the question “Do you feel sick reading in the passenger seat of a car?” and completed a validated motion sickness questionnaire as a measure of motion sensitivity. Lateral canal vHIT testing was performed before and after headshaking; the change in VOR gain was calculated as the primary outcome. Baseline VOR gain was within normal limits across all participants. There was no significant change in VOR gain after headshaking in any group (p=0.264). Patients were 4.3 times more likely to be in the VM group than in the BPPV group if they reported nausea when reading in the passenger seat of a car. We postulate that a headshake stimulus may be insufficient to disrupt cortical interactions and induce a change in VOR gain. Alternatively, changes in VOR gain may only be apparent in the acute phase of VM. Reading in the passenger seat of a car was considered uncomfortable in all VM patients suggesting that this specific question may be useful for the diagnosis of VM.